Sex-based differences in factors associated with bronchial hyperresponsiveness in adolescents with childhood asthma - Kim, Young Hwan (Clin Exp Pediatr, 2021)
BACKGROUND: Bronchial hyperresponsiveness (BHR), an important physiological feature of asthma, is a prognostic marker of childhood asthma. PURPOSE: We aimed to investigate the factors associated with BHR in adolescents with childhood asthma. METHODS: Two hundred and fifteen adolescents (≥13 years of age; 149 males, 66 females) who were diagnosed with asthma during childhood were enrolled, underwent methacholine challenge tests, and were divided into the BHR group (<25 mg/mL of provocation concentration causing a 20% fall in forced expiratory volume in 1 second [FEV(1)] [PC(20)], n=113) or non-BHR group (≥25 mg/mL of PC(20), n=102). We examined longitudinal changes in BHR and the risk factors for its persistence in the 108 adolescents for whom baseline data, including methacholine PC(20) at age 6 years, were available. Multivariate logistic regression analyses were performed to assess the factors associated with BHR in adolescents. RESULTS: Mold sensitization (adjusted odds ratio [aOR], 5.569; P=0.005) and increased blood eosinophil count (aOR, 1.002; P=0.026) were independently associated with BHR in boys but not girls. The odds of BHR decreased by 32% with each 1-year increase in age in boys (aOR, 0.683; P=0.010) but not girls. A reduced FEV(1)/forced vital capacity ratio (<90%) was independently related with BHR in female patients only (aOR, 7.500; P=0.007). BHR decreased with age throughout childhood. A low methacholine PC(20) at age 6 years was independently associated with persistent BHR throughout childhood in male and female patients, whereas early mold sensitization was a risk factor for persistent BHR in male patients only (aOR, 7.718; P=0.028). CONCLUSION: Our study revealed sex-specific differences in the factors associated with BHR in adolescents with childhood asthma. Our findings suggest the risk factors that might affect asthma transition from childhood to adolescence and adulthood.